The crystal structure of 6-bromohexanoic acid, C6H11BrO2 - Ndima Lubabalo; Hosten Eric C.; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C6H11BrO2, monoclinic, P21/n (no. 14), a = 10.6730(14) Å, b = 5.2781(6) Å, c = 14.7781(18) Å, β = 109.610(4)°, V = 784.21(17) Å3, Z = 4, Rgt(F) = 0.0225, wRref(F2) = 0.0564, T = 200(2) K.